Modern and Postmodern Concepts of Reality: Kant and Borges on Emanuel Swedenborg - Vidauskytė, Lina (Problemos, 2007)
The article deals with two different interpretations of the “transcendental” experience of Swedish mystic Emanuel Swedenborg offered by Immanuel Kant and Jorge Luis Borges. From the beginning Swedenborgian experience was questionable. One of the first investigators of Swedenborg‘s texts was Immanuel Kant who strictly criticised the mystic. Kantian own “experience” is exposite in “Universe Theory according to Principles of Newton” (1755) and “Physical Geography” (1802). In a matter of principle Kantian “experience” has no different from experience of Swe denborg. Kant‘s standpoint to Swedish mystic is modern, i.e. the strongest criteria of the reality is a common sense. Contrary to this modern view is exposed postmodern attitude to visions and descriptions of spiritual world of Swedenborg. J. L. Borges represents such standpoint. Borges was influenced by the philosophy of George Berkeley. According to Borges there is no different between real reality and percepted reality.
Keywords: reality, experience, perception, modern, postmodern